Plasma & Astrotheology (Global Journal of Science Frontier Research, 2020)
How did the Superforce come into play? The answer lies in the plasma. In this paper, we consider the plasma and well-established equations. By these equations, we see that the plasma fits well into the theory of Astrotheology.